Practices and perspectives of teacher trainees upon online language education programme - Feryal Cubukcu (Universidade Estadual Paulista Júlio de Mesquita Filho, 2021)
Instructional technologies have been used extensively after the spread of COVID19. Council of Higher Education in Turkey closed down all the universities and embarked on online education by issuing a statement that all universities were free to choose the platform they wished to use. This study aims at discovering how online language teacher education programmes yielded emerging patterns and how teacher trainees' perspectives were in relation with these online language teacher education programmes. To reach this aim, 275 teacher trainees at the Department of English Language Teaching participated in the study and semi-structured interviews were held with them. This discussion illuminates critical issues and attitudes of teacher trainees along with the challenges unique to programmes as a future research agenda.